APPLICATION OF THE "CONDITIONS OF LEARNING" THEORY IN THE TEACHING METHODOLOGY OF FINE ARTS - Emil Raul oğlu Ağayev (Theoretical Hypotheses and Empirical Results, 2024)
Various pedagogical theories should be used in the teaching of fine arts. Each stage of the "Conditions of Learning" theory awakens students’ interest in fine arts. It should be noted that in this pedagogical theory, mainly students learn to write an essay, interact with previous knowledge, and learn the mutual unity of theoretical and practical skills. In this article, the "Conditions of Learning" theory, which plays an important role in the teaching of fine arts, is analyzed.